PENGARUH LINGKUNGAN KERJA NON FISIK, KOMPENASI NON FINANSIAL DAN KEPUASAN KERJA TERHADAP LOYALITAS KARYAWAN PADA PT. KENCANA AMAL TANI PKS - SEBERIDA - Sebastian S '; Marzolina '; Haryetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Kencana Amal Tani PKS - Seberida. The purpose of this study was to determine the effect of non-physical work environment, non-financial compensation and job satisfacation on employee loyality. The study population was 78 employees and is set with models census. Research variables used are the non-physical work environment, non-financial compensation and job satisfacation as independent variables and employee loyality as dependent variable. Methods of data analysis using multiple linear regression analysis aided by SPSS version 21.The results of this study concluded that the variable non-physical work environment, non-financial compensation, and job satisfacition positive and significant effect on employee loyality. In this case the non-phsical work environment, the company should increase activities that can foster a sense of togetherness among employess. Non-financial compensation can be enhanced by company’s employees by giving praise, promotions and awards for excellent employees. Variable empluee satisfacation can be improved by placing the employee in the right position, raises salaries, promotion for excellent employee and make good non physical work environment. With increasing employee loyality, company goal will be achievedKeyword: Non-physical work environment, Non-financial compensation, Job satisfacation, Employee Loyality.